Vegetation dynamics and their relationships with climatic factors in the Qinling Mountains of China. (January 2020) - Wang, Bin; Xu, Guoce; Li, Peng; Li, Zhanbin; Zhang, Yixin; Cheng, Yuting; Jia, Lu; Zhang, Jiaxin
Highlights: The relationships between NDVI and climate factors were analyzed in different time-scales. Elevation and slope are two key topographical factors affecting vegetation growth. Distribution of NDVI change-points had spatial and temporal differences. Abstract: The "China Core" of China's ecosystem, the Qinling Mountains (QM), occupies a special geographical location and has a unique ecosystem. Recently, the growth of vegetation has become an important indicator, reflecting the changes of the ecosystem. The characteristics of spatio-temporal variation of the vegetation and their relationships with climatic factors in the QM were analyzed using the Normalized Difference Vegetation Index (NDVI), based on statistical analysis and Hurst exponent analysis. The results showed that NDVI generally increased over the past 16 years, with increasing NDVI occupying 96.29% of the total study area. The marginal areas of the northern QM were the major regions showing decreasing vegetation growth, while the largest increase in vegetation growth occurred in the northwest. Changes in topographical elements (slope, elevation) had marked impact on vegetation growth, with degraded vegetation being mainly distributed on slopes <30° and at an elevation <1000 m. In the growing season, the relationship between increased precipitation and increased NDVI became weak when average precipitation exceeded 80 mm, whereas the positive effects of average temperature on NDVI increased as the temperature rose. The change-point of NDVI mainly occurred in the southwestern margin and the central-eastern regions of the QM, especially in 2006, 2007 and 2008. This study provides useful information on the vegetation growth status in the QM, and has practical implications for government policy in the vegetated areas.